Phytochemicals profiling, antimicrobial activity and mechanism of action of essential oil extracted from ginger (Zingiber officinale Roscoe cv. Bentong) against Burkholderia glumae causative agent of bacterial panicle blight disease of rice - Gunasena, Mahesh Tiran; Rafi, Amara; Mohd Zobir, Syazwan Afif; Hussein, Mohd Zobir; Ali, Asgar; Kutawa, Abdulaziz Bashir; Abdul Wahab, Mohd Aswad; Sulaiman, Mohd Roslan; Adzmi, Fariz; Ahmad, Khairulmazmi (MDPI, 2022)
Essential oils protect plants, and due to their natural origin, there is much interest in using them as antimicrobial agents. The purpose of this study was to determine the phytochemical constituents of ginger essential oil (GEO), antimicrobial activity, and mode of action against Burkholderia glumae (Bg). In addition, the volatile active compounds (AIs) were studied using GC-MS, FTIR, and Raman spectroscopy. A total of 45 phytochemical components were detected and the most prevalent bioactive compounds were Geranial, 1,8-Cineole, Neral, Camphene, α-Zingiberene, and α-Farnesene. Furthermore, it was found that the most dominant terpenes in GEO were monoterpenes. The diameter zone of inhibition values varied from 7.1 to 15 mm depending on the concentration tested. In addition, the MIC and MBC values were 112.5 µL/mL. Faster killing time and lower membrane potential were observed in 1xMIC treatment compared to 0.5xMIC treatment, whereas the control had the maximum values. From observations of various images, it was concluded that the mode of action of GEO affected the cytoplasmic membrane, causing it to lose its integrity and increase its permeability. Therefore, the antibacterial study and mechanism of action revealed that GEO is very effective in suppressing the growth of B. glumae.